Analysis of Inclusion Education Services for Children with Learning to Read Case Study in Grade III Students (Sainteknol : Jurnal Sains dan Teknologi, 2022)
This study aims to determine the factors that cause children to become dysgraphia and find out the services provided to dysgraphia children in grade III SD 2 Klepu Semarang. This research uses qualitative types and case study designs. The research sample was students with special needs in grade III of SD Negeri Klepu 02 Pringapus District, Semarang Regency. The data collection methods used are interviews, observations, documentation and field notes. The results of this study show that educational services provide several inclusive education programs to overcome children with learning difficulties which include the use of supporting media so that children are more interested in learning and curriculum modifications carried out by class teachers along with special accompanying teachers. In addition, there are several factors that cause children to have learning difficulties due to the lack of attention given by parents to children. As well as the absence of communication between teachers and parents in overcoming the difficulties of learning to read children.